Does the brassinosteroid signal pathway in photomorphogenesis overlap with the gravitropic response caused by auxin?. Issue 11 (2nd November 2014) - Jaroensanti, Naiyanate; Yoon, Jung-Min; Nakai, Yuji; Shirai, Ikuya; Otani, Masato; Park, Seung-Hyun; Hayashi, Ken-ichiro; Nakajima, Masatoshi; Asami, Tadao
Abstract: Brassinosteroid (BR) and auxin co-regulate plant growth in a process termed cross-talking. Based on the assumption that their signal transductions are partially shared, inhibitory chemicals for both signal transductions were screened from a commercially available library. A chemical designated as NJ15 (ethyl 2-[5-(3, 5-dichlorophenyl)-1, 2, 3, 4-tetrazole-2-yl]acetate) diminished the growth promotion of both adzuki bean epicotyls and Arabidopsis seedlings, by the application of either BR or auxin. To understand its target site(s), bioassays with a high dependence on the signal transduction of either BR (BR-signaling) or auxin (AX-signaling) were performed. NJ15 inhibited the photomorphogenesis of Arabidopsis seedlings grown in the dark, which mainly depends on BR-signaling, while NJ15 also inhibited their gravitropic responses mainly depending on AX-signaling. On the study for the structure–activity relationships of NJ15 analogs, they showed strong correlations on the inhibitory profiles between BR- and AX-signalings. These correlations imply that NJ15 targets the downstream pathway after the integration of BR- and AX-signals. Graphical abstract: : A chemical diminished growth promotion by brassinosteroid or auxin. It's target may be downstream after the integration of both signal transductions.